Endonyx toenail onychomycosis caused by Trichophyton rubrum: treatment with photodynamic therapy based on methylene blue dye - Linton Wallis Figueiredo Souza; Simone Vilas Trancoso Souza; Ana Cristina de Carvalho Botelho (Sociedade Brasileira de Dermatologia, 2013)
This study shows the effectiveness of photodynamic therapy based on methylene blue dye for the treatment of endonyx toenail onychomycosis. Four patients with endonyx onychomycosis caused by Trichophyton rubrum were treated with 2% methylene blue aqueous solution irradiated with light emission diode at 630 nm and an energy density of 36 J/cm2 for 6 months at 2-week intervals. The preliminary study showed the effectiveness of this therapy in the treatment of endonyx onychomycosis, and also indicated that the disease can be caused by T. rubrum.